Kollektives Gedächtnis und individuelle Erfahrungen in Beratungshandlungen online im deutsch-polnischen Vergleich - Szwed, Iwona (Stylistyka, 2019)
The analysis of online discussions in Internet forums creates an opportunity to capture traces of collective and individual memory as evidence of affiliation to a specific community. In the paper, the starting point for the analysis is the counselling discourse conducted in specialisedlegal issues in Polish and German Internet forums. One of the elements of traditional face-to-face counselling discourse is the closeness and trust between the counsellor/expert and the person who is asking for advice. Nonetheless, in the case of mediation, the stock of knowledge on the Internet and the ongoing anonymisation of online counselling, it is possible to notice that discourse participants attempt to replace such traditional closeness by referring to their common cultural or historical background of the past. The presented conclusions from the contrasting Polish-German perspective allow an assessment as to what extent the cultural memory of a given community created online is able to replace the traditional closeness and trust in the process of giving advice.